REGRESSION ANALYSIS TO DETERMINE STATURE FROM HAND ANTHROPOMETRY AMONG ILOCANO POPULATION IN PHILIPPINES FOR PERSON IDENTIFICATION - Moorthy, T.Nataraja (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 11 No 1 (2021): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2021.v11.i01.p03, 2021)
Stature determination aids the person identification during forensic investigation. The human hand research is the current topic of interest among forensic scientist, forensic medicine experts and anthropologists. Based on sample size analysis, the study involved consented 60 males and 60 females, age ranged from 18 to 55 years old. Stature and hand lengths measurements were made with Stadiometer and Vernier Calipers for analysis.  From each participant, ten hand length measurements, five from left and five from right hands were taken. The five length measurements in left hand are the inter-distance between the distal traverse crease of the wrist (LH) and tip of thumb (T), index finger (I), middle finger (M), ring finger (R) & little finger (L), as abbreviated LHT, LHI, LHM, LHR and LHL. Similarly, the right hand lengths indicated as RHT, RHI, RHM, RHR, and RHL.  The data were statistically analyzed by using SPSS software, version 23 and column chart. The information about age, gender, name, and place of origin of the participants was coded for easy reference. This study finally developed regression equations to determine stature from hand anthropometry among Ilocano population in Philippines for person identification